Teseng: Implementation of justice values in profit-sharing agreements based on the local wisdom of the Bugis Makassar community - Salle, Salle; Zainuddin, Zainuddin; Aini, Syifa Nur; Buana, Andika Prawira (Jurnal Hukum Novelty, 2024)
Introduction to the Problem: This paper explores the teseng agreements and the Implementation of Justice Values in profit-sharing agreements based on local wisdom of Bugis Makassar Community. The teseng principle is operationalized through the utilization of a streamlined system that adheres to the model established within the Bugis-Makassar community. The community will collaborate with one party as the Pa'bere teseng and the other as the Pa'teseng in this partnership. The legal issue in the research is the implementation of justice values in the teseng agreement. Purpose/Study Objectives: The purpose of this research is to analyse the practice of teseng agreements in Bugis-Makassar community and the implementation of justice values in teseng agreements. This research will provide the parties with a better understanding of the significance of the justice values in the teseng agreement. Design/Methodology/Approach: This study constitutes normative and empirical legal research. The data used in this research is primary data obtained through in-depth interviews with Pa’bere Teseng (landowners or livestock) and Pa’teseng (cultivator or ranchers). Secondary data is used as a complement, namely data collection techniques through literature studies. Findings: Teseng is a mutual agreement that binds two parties - the investor and the cultivator. In the teseng system, the Pa’bere Teseng (landowners or livestock) gives land or livestock animal to Pa’teseng (cultivator or ranchers) and receives a share of the proceeds from his efforts. The teseng agreements is based on trust and agreement between the Pa’bere Teseng and the Pa’teseng. The teseng system reflects the values of justice by eliminating the terms employer and laborer. The Pa’bere Teseng and the Pa’teseng have the same position under the law. This teseng system creates proportional justice, allocating a share to individuals based on their services or contributions. According to the principle of proportional justice, the degree of success achieved by an individual is equivalent to the degree of effort invested in that person. Paper Type: Research Article